2015
DOI: 10.1615/interfacphenomheattransfer.2016014801
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measurement of the Electric Forces Acting on a Growing Gas Bubble in Quasi-Static Conditions

Abstract: This work was aimed at measuring the resulting electric forces acting on a gas bubble growing quasistatically, with gas supplied to it through a circular orifice, and to compare them with their theoretical counterparts. An experimental apparatus has been set up, consisting essentially of an orifice drilled in a flat stainless steel plate submerged in the test fluid (FC-72). A dedicated gas injection system allowed creating slowly growing or even static bubbles of any desired volume, up to the detachment volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Their findings suggest that plausible magnitudes for all the external forces and resulting bubble acceleration can only be precisely quantified if the bubble shape is accurately known at all times. Several studies demonstrated that these conclusions also apply to quasi-static injection of bubbles through orifices (Duhar & Colin 2006; Di Marco, Giannini & Saccone 2015; Lebon, Sebilleau & Colin 2018). One major source of uncertainty comes from contact line surface tension forces.…”
Section: Introductionmentioning
confidence: 88%
“…Their findings suggest that plausible magnitudes for all the external forces and resulting bubble acceleration can only be precisely quantified if the bubble shape is accurately known at all times. Several studies demonstrated that these conclusions also apply to quasi-static injection of bubbles through orifices (Duhar & Colin 2006; Di Marco, Giannini & Saccone 2015; Lebon, Sebilleau & Colin 2018). One major source of uncertainty comes from contact line surface tension forces.…”
Section: Introductionmentioning
confidence: 88%
“…4 to compute the electric force is that the Maxwell stress tensor only depends on the local value of the electric field, and it does not require determining charge density distributions or dealing with discontinuities at the liquid-vapor interface. This facilitates the evaluation of the electric force, that in practice is performed by numerically solving the electrostatic problem in the fluid domain and then using the values of the electric field at the liquid-vapor interface in the liquid side [26,30]. In this work, we aim to investigate the integral momentum balance of the vapor bubble based on high-speed video measurements only.…”
Section: Investigation Of the Integral Momentum Balance Of The Vapor ...mentioning
confidence: 99%
“…To partially fill this knowledge gap, we investigated the effect of electric field on the dynamics of bubble growth in microgravity conditions by means of an integral momentum balance (IMB) analysis. A similar approach has been adopted by Di Marco et al in [26,30]. Recently, Garivalis and Di Marco [31] reformulated the integral force balance in a different form, where however the determination of the electric force required an "a priori" numerical solution of the laws of electrostatics in the dielectric fluid.…”
Section: Introductionmentioning
confidence: 99%
“…see Refs. [24][25][26]) have revealed that the resultant of the "classical" forces (for negligible growth forces) prior to detachment is practically null. This observation suggests that the issue could be in the description of the external forces, and in particular the growth force, rather than due to the absence of an additional London-Van der Waals reaction force.…”
Section: Force Definition Modelmentioning
confidence: 99%